In situ treatment of a dilute chlorinated solvent plume in an acidic aerobic aquifer. Issue 2 (28th February 2020) - Alexander, Matthew
Abstract: In situ bioremediation was selected in the Record of Decision (ROD) as the remedial technology for a 29‐acre dilute, acidic and aerobic, chlorinated solvent plume (principally trichloroethylene [TCE] and 1, 1‐dichloroethylene) for a Superfund site located in central New Jersey. Implementation of the remedy at full‐scale began in late 2010, using reductive dechlorination and bioaugmentation, and treatment has continued steadily over the last 9 years. The amendments injected include electron donor and alkaline (bicarbonate) buffer solution and, once anaerobic aquifer conditions became established, a bioaugmentation culture. Amendment injections occurred in multilevel injection wells (IWs), to maintain control over the vertical interval of amendment delivery. The areal coverage of the plume has been reduced by 59% based on the 10 µg/L TCE isocontour and the contaminant mass has been reduced by 79% through the 9 years of treatment. Lessons learned from this project include the need for bioaugmentation in the acidic aquifer and an efficient and effective manner of well construction and amendment injection using multiscreen single casing IWs and packer systems. Additional lessons learned include differences in longevity of the electron donor amendment versus the bicarbonate neutralization additive, and the need for varied amendment delivery techniques (IWs, direct injection, horizontal well installation) in selected lower permeable zones to attain treatment.